Analysis of Remoteness Effect of Indigenous Coconut (Cocosnucifera L.) Commodity on Farmers Profit at Tidal Lowland Area of Jambi Province-Indonesia - Ningsih R.; F. Sjarkowi; M. Sufri; D. Adriani; E. Wildayana (Sriwijaya Journal of Environment, 2017)
The research objectives were to analyze pressure magnitude condition in forms of: 1) the excess supply of indigenous coconut commodity on farmers profit and 2) remoteness location of indigenous coconut plantation on farmer’s profit. The method used in this research was field survey which was conducted from November 2015 to March 2016at two Districts of Tanjung Jabung Barat and Tanjung Jabung Timur of Jambi Province distributed at several Sub districts. Data was collected by using questionnaires for 100 respondents and was analyzed by using software of SPSS 20.The results showed the following facts: 1) indigenous coconut had characteristics of excess supply and mostly found at isolated plantation sites, 2) each characteristics of indigenous coconut commodity had negative effect on profit received by farmers. Therefore, local government policy is required to manage specific characteristics of indigenous coconut commodity at this area in form of proper policy strategy such as creating the added value of product through processing of coconut derivative product (product diversification) especially at famers level which located close to plantation sites.Key words: Remoteness, indigenous coconut, profit, farmer, tidal lowland